STUDI USAHA TRANSPORTASI WISATA BAHARI KALIMAS KELURAHAN CALACA KOTA MANADO PADA MASA PANDEMIK COVID-19 - Salanggamo, Verki; Andaki, Jardie A.; Wasak, Martha P.; Sondakh, Srie J.; Aling, Djuwita R.R.; Rangan, Jetty K. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2021)
AbstractThe formulation of the problem in this study, namely how is the state of the inter-island ecotourism transportation business at the Kalimas Tourism Port, Calaca Village, Manado City in the face of the Covid-19 pandemic. Meanwhile, the purpose of this research is to study the state of the inter-island ecotourism transportation business at the Kalimas Tourism Port, Calaca Village, Manado City in the face of the Covid-19 pandemic.This research uses a descriptive type of research based on case study research, in this case the inter-island ecotourism transportation business in the tourist port of Kalimas, Calaca Village, Manado City. This research uses descriptive qualitative and quantitative approaches, namely research procedures that produce descriptive data in the form of written words or from people's spoken words and observed behavior. The approach is directed to the background of the object and the individual holistically (intact). Respondents in this study are people who carry out inter-island ecotourism transportation businesses at the Kalimas tourism pierThe results of the study can be concluded: 1) the inter-island transportation business in Kalimas has been started since 2016, every day each boat can carry a maximum of up to 30 people along with their luggage, the fare per passenger is Rp. 20,000.00 and for luggage, a rate of Rp. 2,000.00 for all types of goods; 2) during the Covid-19 pandemic, visits from foreign tourists were prohibited, but local residents were still allowed to travel between islands; and 3) during the new normal period, tourist transportation activities using motorized boats could already be carried out including foreign tourists by implementing a strict Covid-19 Protap, but the number of visits was still insufficient.Key words: motorized boat, Kalimas tourism pier, transportation, ecotourismÂ Â AbstrakRumusan masalah dalam penelitian ini, yaitu bagaimana keadaan usaha transportasi ekowisata antar pulau di Pelabuhan Wisata Kalimas Kelurahan Calaca Kota Manado dalam menghadapi pandemik covid-19. Sedangkan tujuan penelitian ini, yaitu mempelajari keadaan usaha transportasi ekowisata antar pulau di Pelabuhan Wisata Kalimas Kelurahan Calaca Kota Manado dalam menghadapi pandemik covid-19.Penelitian ini menggunakan jenis penelitian yang bersifat deskriptif dengan dasar penelitian studi kasus, dalam hal ini usaha transportasi ekowisata antar pulau di Pelabuhan wisata Kalimas Kelurahan Calaca Kota Manado. Penelitian menggunakan pendekatan deskriptif kualitatif dan kuantitatif, yaitu prosedur penelitian yang menghasilkan data deskriptif berupa kata-kata tertulis atau dari lisan orang-orang dan perilaku yang diamati. Pendekatan diarahkan pada latar belakang objek dan individu tersebut secara holistic (utuh). Responden dalam penelitian ini ialah masyarakat yang melakukan usaha transportasi ekowisata antar pulau di dermaga wisata KalimasHasil penelitian dapat disimpulkan : 1) usaha Transportasi Antar Pulau di Kalimas telah dimulai dari tahun 2016 setiap harinya setiap perahu dapat mengangkut maksimal sampai dengan 30 orang beserta barang bawaan, tarif per penumpang yaitu Rp. 20.000.00 dan untuk barang bawaan di bebankan tarif Rp. 2.000.00 untuk semua jenis barang; 2) pada masa pademik covid-19 terjadi pelarangan kunjungan dari turis asing, namun penduduk lokal masih diizinkan melakukan perjalanan antar pulau; dan 3) pada masa new normal kegiatan transportasi wisata menggunakan perahu bermotor sudah dapat dilakukan termasuk turis asing dengan menerapkan Protap Covid-19 yang ketat, namun jumlah kunjungan masih kurang.Kata kunci: perahu bermotor, dermaga wisata Kalimas, transportasi, ekowisata